2012
DOI: 10.1111/j.1600-0501.2011.02390.x
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of cone‐beam computed tomography to assess bone density at dental implant recipient sites: a histomorphometric analysis by micro‐CT

Abstract: RBD assessed by CBCT has a strong positive correlation with BV/TV assessed by micro-CT at the site of dental implants in the maxillary bones. Pre-operative estimation of density values by CBCT is a reliable tool to objectively determine bone density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
122
3
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(143 citation statements)
references
References 23 publications
5
122
3
13
Order By: Relevance
“…Shapurian et al 16 reported that knowledge of the Hounsfield value as a quantitative measurement of bone density can be helpful as a diagnostic tool. Gonzales-Garcia and Monje 27 conducted a study on the reliability of cone-beam computed tomography (CBCT) for evaluating radiographic bone density. They claimed that CBCT has a strong positive correlation with micro-CT and is a reliable tool for determining bone density.…”
Section: Sem Analysesmentioning
confidence: 99%
“…Shapurian et al 16 reported that knowledge of the Hounsfield value as a quantitative measurement of bone density can be helpful as a diagnostic tool. Gonzales-Garcia and Monje 27 conducted a study on the reliability of cone-beam computed tomography (CBCT) for evaluating radiographic bone density. They claimed that CBCT has a strong positive correlation with micro-CT and is a reliable tool for determining bone density.…”
Section: Sem Analysesmentioning
confidence: 99%
“…28 Similar measurements from CBCT scans, even if dependent on the specific device being used, still correlate with histomorphometric bone density and primary implant stability. [29][30][31][32] However, bone density may show ample variations even in contiguous points of the maxillary bone, and this raises the question of whether absolute or relative bone density values assessed on preoperative CTs or CBCTs will correspond to the ones at the actual placement sites, since these may not overlap perfectly with the ones preplanned on the digital scans. 12 Even using stereolithographic guides for implant placement may not solve this issue since significant deviations from the preplanned placement positions may still be observed, the greatest errors being found when patients move during the CT scans, resulting in significant divergence at the level of the head and apex of the implants, and also in angular deviation.…”
mentioning
confidence: 99%
“…Cone beam computed tomography (CBCT) was originally developed in the early 1980s for angiography [16,17,36,41,53,69], and more than a decade later it was applied to dentomaxillofacial diagnostics. The main advantages of CBCT are relatively high-resolution acquisition and, compared with conventional CT, lower radiation doses with smaller and less expensive equipment [12,16,17,36,[44][45][46][47][48][49]53,69,70,79].As was discussed in Section 5.1, from a technical point of view, the limitation of image quality by dental CBCT technology is dependent on the increased X-ray scatter. This not only increases patient dose but also is a principal contributor to reduced contrast resolution and increased noise in CBCT images [37,46,53,69,71], therefore influencing the density values [13,16,17,29,30,36,37,39,[47][48][49][50]53,66,69,70].…”
mentioning
confidence: 99%
“…D: Square form basic projection image of the pyramid shape beam instrument (iCAT Classic). The 3D reconstructed image is cylindrically shaped [32,36].The main advantages of dental CBCT are relatively high-resolution acquisition and, compared with conventional CT, lower radiation doses with smaller and less-expensive equipment [11,12,16,17,32,36,[44][45][46][47][48][49][50][51].The next milestone in development was in 2003, when J. Morita Mfg Corporation produced equipment with relatively small volume. In this instrument the patient was already in a seated position (Figure 15 B).…”
mentioning
confidence: 99%
See 1 more Smart Citation